Fullerene C60 Decreases Inflammation, Oxidative Stress and Apoptosis Induced by 7,12-Dimethylbenz[a]Anthracene (DMBA) in Muscle Tissue Via Caspase-3 and NRF-2 Protein Signaling Pathway - Aslan, Abdullah; Beyaz, Seda; Gok, Ozlem; Ozercan, Ibrahim Hanifi; Agca, Can Ali (Springer, 2024)
Fullerene C-60 exhibits potent antioxidant anti-inflammatory activities as well as anticancer activities. In this study using 60 Wistar albino female rats (n = 60, 8 weeks old), they rats were divided into 4 groups, including 15 rats each. The groups were arranged as follows: (i) Control Group: Group fed with standard diet; (ii) C-60 Group: C-60 (1.7 mg/kg bw, oral gavage); (iii) DMBA (7,12-dimethylbenz[a]anthracene) Group: DMBA (45 mg/kg bw, oral gavage); (iv) C-60 and DMBA Group: C-60 (1.7 mg/kg bw, oral gavage) and DMBA (45 mg/kg bw, oral gavage) group. DMBA increased the malondialdehyde levels in muscle tissue, while decreasing GSH and CAT levels; however, treatment with fullerene C-60 reversed these effects. In addition, the oral administration of fullerene C-60 increased caspase-3 and Nrf-2 protein expression and significantly decreased Bcl-2, NF-kappa B, TNF-alpha, COX-2 and p38 alpha (MAPK) protein expression in C60 + DMBA compared to the DMBA group. Moreover, histopathological imaging revealed that the oral administration of fullerene C-60 decreases inflammatory cells, edema formation, and hydropic degeneration in the muscles. Taken together, the results of the present study indicated that fullerene C-60 nanoparticle provides effective protection by preventing muscle tissue damage.
Keywords: apoptosis; COX-2; DMBA; fullerene C-60; muscle damage